Variations in the power output of the Piezon‐Master 400 ultrasonic endodontic unit - Ahmad, M; Roy, RA; Kamarudin, AG (Wiley, 1994)
The present study was undertaken to see if there was any variability in the power output of Piezon‐Master 400 ultrasonic files when driven using different generators, tranducers and file holders. The displacement amplitude of the oscillating tip of the file in air was used as a measure of the power output. The results showed that there was considerable variability in the power output of Piezon‐Master 400 ultrasonic files of similar size and length when driven using different generators, transducers and file holders. In consideration of this, it is recommended that a calibration device be incorporated in the ultrasonic unit so that the operator will have some knowledge of when the unit is working at its maximum efficiency.